ON SUPER EDGE-MAGIC DEFICIENCY OF CERTAIN GRAPHS - Chaudhary M.U.; Sarfraz A.A. (Utilitas Mathematica, 2020)
R. M. Figueroa^ Centeno et ol. brought out the idea of super edge-magic deficiency, /i#(<7), of simple graph which is the minimum integer n € N|J0 for which G admits a super edge-magic labeling or it is +00 if no such n exists. Also, n = 0 implies that G is super edge-magic. In this article, we study the super edge-magic deficiency of disjoint unions of graphs mainly copies of cycles with trees and forests. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.